Український національний музей-архів у Празі: історія створення та функціонування - Мельник, Роман; Мельник, Віра (Видавництво Львівської політехніки, 2017)
The defeat of the Ukrainian national liberation revolution of 1917-1921. Led to a wave of Ukrainian immigration to European countries. The largest in the interwar period was Ukrainian community in the newly created Czechoslovak Republic where the See of the place - Poland, Romania, Austria, Turkey, Bulgaria and other countries - has left many Ukrainian immigrants, including representatives of political, scientific and military elite. In 1920-1930 gg. When in Ukraine, exhausted by civil war, divided between Poland and Bolshevik Russia was actually established occupation regime that strictly vykorinyuvav all Ukrainian, Prague has become the world center of Ukrainian national socio-political, cultural and scientific life.
Keywords: музей-архів; Прага; архівний документ; експонат; еміграція